Pengembangan Bahan Ajar pada Matakuliah Statistik Infrensial Berbasis Bimbingan dan Konseling - Muh. Mansyur Thalib; Abd. Munir; Hasan Hasan (Bulletin of Counseling and Psychotherapy, 2022)
The purpose of this study was to produce teaching materials for infrensial statistics in the Guidance and Counseling study program. The collection of teaching material assessment data from experts uses a closed (direct) questionnaire, while student response data uses a questionnaire through the "google form" application and exam questions via "whatsapp". The research data were analyzed descriptively, namely the addition technique, calculating the average, categorization, and the use of assessment guidelines. The results of the development of teaching materials include: (1) the initial section consists of: cover, cover page, validation page, foreword, table of contents, list of tables, and list of attachments, (2) teaching materials of infrensial statistics are divided into 12 parts (main material), (3) each section contains: description, material description, summary, exercises and questions, feedback, bibliography and practice answer key (attached). The results of the assessment of the developed teaching materials show that the teaching materials are good, the presentation of the teaching materials is good, the design of the teaching materials is good, the language of teaching materials declared suitable for use is very good, the practicality of the teaching materials is good. The effectiveness of the use of teaching materials aspects of learning motivation is effective, aspects of student learning activity are effective, and aspects of student success/graduation using teaching materials are effective.